2000
DOI: 10.2337/diacare.23.6.859
|View full text |Cite
|
Sign up to set email alerts
|

Plasma brain natriuretic peptide levels in normotensive type 2 diabetic patients without cardiac disease.

Abstract: Sane , Saito H: Endogenous glucose production and glucose effectiveness in type 2 diabetic subjects derived from stablelabeled minimal model approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
9
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 0 publications
2
9
1
Order By: Relevance
“…1 (C), even the level of HbA1c could not change the plasma BNP level, although there were no differences in other parameters, including age, duration of diabetes, BMI, or the levels of blood pressure or lipid (data not shown). Differently from our finding, Isotani et al have reported that there was a negative correlation between the levels of plasma BNP and HbA1c [14]. With regard to the reason, they speculated about the presence of plasma osmotic diuretics by hyperglycemia, but it is plausible to assume that 7.6% of HbA1c was not high enough to induce diabetic polyuria.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…1 (C), even the level of HbA1c could not change the plasma BNP level, although there were no differences in other parameters, including age, duration of diabetes, BMI, or the levels of blood pressure or lipid (data not shown). Differently from our finding, Isotani et al have reported that there was a negative correlation between the levels of plasma BNP and HbA1c [14]. With regard to the reason, they speculated about the presence of plasma osmotic diuretics by hyperglycemia, but it is plausible to assume that 7.6% of HbA1c was not high enough to induce diabetic polyuria.…”
Section: Discussioncontrasting
confidence: 56%
“…These reports appear to suggest that BNP might be related to the presence of diabetic complications. On the other hand, contrary to these reports, no other trials have demonstrated the existence of any relationship between the plasma BNP level and complications, such as albuminuria and reti-nopathy, in normotensive diabetic patients without cardiac diseases [14,15].…”
mentioning
confidence: 47%
“…In previous epidemiological studies regarding the association BNP and renal function, plasma BNP ranged from 10.8 to 46.3 ng/dL [5][6][7][8][9]. The discrepancies among these studies may be explained, at least in part, by differences in sample size; the definition of renal function; characteristics such as age, sex, race, BMI, prevalence of coronary heart diseases, subclinical heart failure and hypertension; and other confounding factors.…”
Section: Discussionmentioning
confidence: 87%
“…On the other hand, in a Japanese study of 100 normotensive patients with type 2 diabetes mellitus, BNP level was not positively associated with microalbuminuria [8]. In another Japanese study of 100 normotensive patients with type 2 diabetes mellitus, BNP level was not associated with proteinuria [9]. In a Japanese cohort study of 97 patients with type 2 diabetes mellitus and microalbuminuria, low BNP at baseline was a predictor for remission of diabetic nephropathy [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation